Type-specific antigenic determinants on the major external glycoprotein of high- and low-oncogenic murine mammary tumor viruses. - Teramoto, Y A (1977)
We recently showed that the 52,000-dalton external glycoprotein (gp52) of the highly oncogenic mouse mammary tumor viruses (MMTVs) of RIII, GR, and C3H mice contains both type- and group-specific antigenic determinants. This was demonstrated by using a competition radioimmunoassay with 125I-externally labeled virions and antisera to the gp52 of MMTV from RIII mice (Proc. Natl. Acad. Sci. U.S.A. 74:3564-3568, 1977). We report here that we were able to distinguish between the gp52's of the high-oncogenic MMTV of C3H mice [MMTV(C3H)] and the low-oncogenic MMTV of that same mouse strain [MMTV(C3Hf)]. This was accomplished by use of a competition radioimmunoassay with 125I-externally labeled virions of MMTV(C3H) and antisera prepared against MMTV(C3H). A comparison of the intact virion and purified gp52 radioimmunoassays showed that MMTV type-specific differences were enhanced with the intact virion radioimmunoassay. These differences were further magnified with appropriately absorbed antisera. These findings thus allow an immunological distinction between the surface glycoproteins of a low-oncogenic endogenous and a high-oncogenic exogenous MMTV of the same mouse strain.